2019
DOI: 10.4103/joacp.joacp_353_17
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparative study between prewarming and cowarming to prevent intraoperative hypothermia

Abstract: Background and Aims: Inadvertent perioperative hypothermia defined as the perioperative core temperature of <36°C is a common problem in day-to-day anesthesia practice. It is not clear from the literature whether prewarming, that is, initiation of convective warming of the patient at a time point prior to induction of anesthesia is superior or comparable to cowarming, that is, initiation of convective warming simultaneously with induction of anesthesia. We conducted this study to find whether cowa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Shenoy et al [ 18 ] conducted a study on 60 patients in which the medians of core temperature (°C), peripheral temperature (°C), and core to peripheral temperature gradient (°C) at the baseline were identified as 36.1 (0.8), 32.9 (2.4), and 3.4 (1.7, 4.5) in the pre-warming group, while they were identified as 36 (0.58), 32.1 (2.8), and 3.5 (1.8, 5.1), respectively, in the co-warming group, which was an increased median as compared to our study results. Shenoy et al [ 18 ] showed similar results to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Shenoy et al [ 18 ] conducted a study on 60 patients in which the medians of core temperature (°C), peripheral temperature (°C), and core to peripheral temperature gradient (°C) at the baseline were identified as 36.1 (0.8), 32.9 (2.4), and 3.4 (1.7, 4.5) in the pre-warming group, while they were identified as 36 (0.58), 32.1 (2.8), and 3.5 (1.8, 5.1), respectively, in the co-warming group, which was an increased median as compared to our study results. Shenoy et al [ 18 ] showed similar results to our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 27 , 28 ] A previous study investigating only abdominal surgeries reported that co-warming was as effective as prewarming in preventing intraoperative hypothermia. [ 29 ] The possibility of temperature loss was mainly due to intraoperative hypothermia which was minimized by the continued intraoperative warming in their study. [ 29 ] However, the most reasonable explanation is that hypothermia can only be effectively treated by intraoperative active warming after a core-to-peripheral temperature redistribution phase.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] The possibility of temperature loss was mainly due to intraoperative hypothermia which was minimized by the continued intraoperative warming in their study. [ 29 ] However, the most reasonable explanation is that hypothermia can only be effectively treated by intraoperative active warming after a core-to-peripheral temperature redistribution phase. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Kejadian hipotermia merupakan salah satu komplikasi yang paling sering terjadi selama fase perioperatif. Hipotermia dikondisikan sebagai kondisi tubuh pada suhu di bawah 36°C (Shenoy, 2019). Sebanyak 50-90 % dari semua pasien dengan pembedahan mengalami hipotermia selama fase perioperatif (National Institute for Health and Care Excellence, 2016).…”
Section: Latar Belakangunclassified